Improvement of Social Skills in Early Childhood THROUGH THE ROLE-PLAYING METHOD - Miftakul Jannah (Journal of Art and Creativity in Early Childhood Education, 2025)
Early childhood is in a golden age where they must receive various stimulation and various learning received from both the family environment and society, whether intentionally or unintentionally. At an early age, children's basic abilities are developed to become the initial foundation for the child's further growth and development, including the child's social skills which form the child's character in the future. This article aims to describe improving the social skills of early childhood through role playing methods. The research method used in this article is literature review, by searching, collecting and selecting journal articles as library material which are then analyzed to solve a problem. The research results obtained show that children's social skills can be improved through role playing methods, such as children being able to work together with friends, being able to interact well, being able to control themselves, being able to empathize, being able to obey rules and being able to respect other people. So the role playing method is an effort to improve children's social skills.